Ways of structure building - Uribe-Etxebarria, Myriam; Valmala, Vidal (Oxford : Oxford University Press, 2012)
This volume addresses some of the most important approaches to the following key questions in contemporary generative syntactic theory: What are the operations available for (syntactic) structure-building in natural languages? What are the triggers behind them? and Which constraints are involved in the operations?
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references and index.
Keywords: Structural linguistics; Grammar, Comparative and general -- Syntax